Genome sequencing of ‘Fuji’ apple clonal varieties reveals genetic mechanism of the spur-type morphology - Yudong Cai; Xiuhua Gao; Jiangping Mao; Yu Liu; Lu Tong; Xilong Chen; Yandong Liu; Wenyan Kou; Chuanjun Chang; Toshi Foster; Jialong Yao; Amandine Cornille; et al. (Nature Communications)
Abstract Somatic variations can give rise to bud sports with advantageous traits, serving as the foundation for bud sport breeding in perennial plants. Here, we report a fully phased genome assembly of ‘Fuji’ apple, enabling comprehensive identification of somatic variants across 74 clonally propagated ‘Fuji’ varieties. Phylogenetic analysis indicates that spur-type and early-maturation traits in ‘Fuji’ sport varieties arise from multiple independent events. Several putative functional somatic variants have been identified, including a spur-type-specific deletion in the promoter of the TCP transcription factor gene MdTCP11. DNA methylation level of the deletion-associated miniature inverted-repeat transposable element is lower in spur-type varieties compared to standard-type varieties, while the expression of MdTCP11 is significantly higher. Overexpression of MdTCP11 in apple decreases plant height, highlighting its important role in the development of spur-type apple varieties. This study sheds light on the cloning history of ‘Fuji’ and provides valuable resources for apple breeding.